The impact of civil commitment laws for substance use disorder on opioid overdose deaths - Cochran, Phillip; Chindavong, Peter S.; Edelenbos, Jurian; Chiou, Amy; Trulson, Haylee F.; Garg, Rahul; Parker, Robert W. (Frontiers in Psychiatry, 2024)
Objective: Our study analyzed the impact of civil commitment laws for substance use disorder (SUD) on opioid overdose death rates (OODR) from 2010-21. Methods: We used a retrospective study design using the CDC Wide-ranging Online Data for Epidemiologic Research (WONDER) dataset to analyze overdose death rates from any opioid during 2010-21 using ICD-10 codes. We used t-tests and two-way ANOVA to compare the opioid overdose death rates between the states with the law as compared to those without by using GraphPad Prism 10.0. Results: We found no significant difference in the annual mean age-adjusted OODR from 2010-21 between states with and without CC SUD laws. Before the COVID era (2010-19), the presence or absence of CC SUD law had no difference in age-adjusted OODR. However, post-covid during 2020-21, there was a significant increase in OODR in states with a CC SUD law compared to states without the law (p=0.032). We also found that OODR increased at a faster rate post-covid among both the states with CC laws (p<0.001) and the states without the law (p=0.019). Conclusions: We found higher age-adjusted OODR in states with a CC SUD law which could be due to the laws being enacted in response to opioid crisis or physicians' opposition to or unawareness of the law’s existence leading to underutilization. Recent enactment of CC SUD law(s), a lack of a central record for recording relapse rates, and disparities in opioid overdose rate reductions uncovers multiple variables potentially influencing OODR. Thus, further investigation is needed to analyze the factors influencing OODRs and long-term effects of the CC laws.